Rancang Bangun Sistem Informasi Penggajian Pegawai Honorer Pada UPTD Bidang Pengelolaan Persampahan Wilayah IV Kabupaten Bekasi Berbasis Website - Bagas Wilaksono; Putri Anggun Sari; Eko Budiarto (DPPM Universitas Pelita Bangsa, 2022)
The UPTD for Waste Management Region IV Bekasi Regency Government is a Service that is engaged in the Cleaning Sector. In this field the salary calculation is still using the manual method, namely by using a book and still referring to using Ms.Word and Ms.Excel. so that there are often errors in the process of calculating the salaries of honorary employees. The purpose of this research is to build a website-based payroll information system for temporary employees in order to assist in the process of calculating the salaries of honorary employees. The method used in this research is the waterfall method, because in this method, in building a system, the process is systematic and sequential. This study resulted in a computerized payroll information system to provide information such as employee data information, position data, and payroll data so that it can be concluded that the existence of an employee payroll information system can facilitate the process of calculating salaries accurately and quickly. Keywords : Information System, Waterfall, Website